Prvý oddíl čtrnáctého dodatku Ústavy Spojených států: původní význam a výklad - Jaroslav Ženíšek (Právněhistorické studie, 2023)
The paper analyzes the first section of the Fourteenth Amendment to the United States Constitution and its four key clauses – the citizenship clause, the priviliges or immunities clause, the due process clause and the equal protection clause. Special attention is paid to the debates of the members of the 39th Congress which offer an insight into the original understanding of terms and phrases used in the text of the Amendment and that make possible to understand the context of its origin. The paper tries to describe the most likely original meaning of the individual clauses of the first section and analyze their possible various interpretations that often stand in direct opposition. While it can be reasonably assumed that during the times of the passing and ratification of the Amendment its objective was fairly limited, reflecting the post-war political reality in the United States, during the decades following ratification the Amendment started to be applied to issues that until then had been completely in the hands of the legislatures and depending on the democratic discussion on both federal and state level. The authors quoted in this paper can not be assigned to just one method of interpretation and legal philosophy, to the contrary, the paper aims to confront different views on the Amendment and its original meaning and based on it reach a conclusion; therefore both the view seeing the meaning of the Amendment as limited, held for example by professors Charles Fairman and Raoul Berger, and the perspective that sees its objectives as broader, represented for example by professors Michael Kent Curtis and Randy Barnett, are mentioned.